2017
DOI: 10.1038/s41598-017-16274-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of thrombus volume for recanalization in stent retriever thrombectomy

Abstract: This retrospective study investigated whether the volume or density of the thrombus is predictive of recanalization in stent retriever (SR) treatment. Consecutive patients treated with SR thrombectomy as the first endovascular modality were enrolled. The thrombus volume and density were measured on thin-section noncontrast computed tomography using 3-dimensional software. The patients were grouped by recanalization status and the number of SR passes. Among 165 patients, recanalization was achieved with the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
(41 reference statements)
2
31
3
Order By: Relevance
“…Especially for patients with ICA occlusions mSAVE seems to be a promising approach as the rate of complete and successful reperfusion after a single pass was 46% and 73%, respectively. In a recent study from Baek et al, only 22% of ICA occlusions were successfully reperfused after one attempt and the rate of overall successful reperfusion (which both were graded as modified TICI) was lower compared to our results (76% vs. 82%) [16]; additionally, in 29% of the successfully reperfused patients four or more passes were necessary. In comparison to our recent results with SAVE, the first-pass and overall complete reperfusion rate is also higher in ICA occlusions (26% and 49%, respectively) [9].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Especially for patients with ICA occlusions mSAVE seems to be a promising approach as the rate of complete and successful reperfusion after a single pass was 46% and 73%, respectively. In a recent study from Baek et al, only 22% of ICA occlusions were successfully reperfused after one attempt and the rate of overall successful reperfusion (which both were graded as modified TICI) was lower compared to our results (76% vs. 82%) [16]; additionally, in 29% of the successfully reperfused patients four or more passes were necessary. In comparison to our recent results with SAVE, the first-pass and overall complete reperfusion rate is also higher in ICA occlusions (26% and 49%, respectively) [9].…”
Section: Discussioncontrasting
confidence: 87%
“…While in a post hoc analysis of the ASTER trial it was shown that successful reperfusion was less frequently achieved in patients with a low CBS, Treurniet et al found no evidence that CBS modifies the effect of intra-arterial treatment in the Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands (MR CLEAN) cohort [5,21]. In our opinion, it is reasonable to assume that thrombus volume is an independent factor of successful reperfusion [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several possible causal relations between prolonged ATG intervals and reduced rates of TICI 2b-3 have previously been discussed, 5 such as thrombus modification over time (volume/extension, 17 histological features 18 ), which might influence mechanical reperfusion efficacy. 19 , 20 At first sight, however, this may be contradictive to the only small association between STA and TICI 2b-3 because STA does usually constitute by far more of the time interval elapsed between symptom onset and the start of the intervention (≈2/3 in our cohort). Bourcier et al argued that the effect of STA may be diluted by uncertainties regarding the exact time point of symptom onset.…”
Section: Discussionmentioning
confidence: 60%
“…6 Other studies have failed to confirm these findings, however, and overall the literature has been conflicting with some studies showing no association between clot density and recanalization with stent retrievers or aspiration. 16,17 However, when considering the use of stent retrievers only (as opposed to aspiration thrombectomy), Mokin et al reported in their series a positive association between higher-density clots on NCCT and rate of SR using the Solitaire (eV3, Irvine, CA, USA) stent retriever. 4 Thrombus perviousness has recently been described as a method of estimating how permeable a clot is using enhancement and washout measures using arterialand delayed-phase CTA.…”
Section: Discussionmentioning
confidence: 99%